562 THE EFFECT OF IONISING-RADIATION AND THE TUMOUR MICRO-ENVIRONMENT (TME) ON TREATMENT NAIVE ESOPHAGEAL ADENOCARCINOMA PATIENT T CELL FUNCTION AND ACTIVITY. (14th September 2020) - Donlon, N; Sheppard, A; Davern, M; Donohoe, C; Ravi, N; Reynolds, J; Lysaght, J
Abstract:  : There is extensive literature demonstrating CD8+ T cells are essential for initial tumour control following radiation, however, effects are reduced after time due to T cell exhaustion and a lack of release Damage Associated Molecular Patterns (DAMPS) which are essential for anti-tumour immune responses. In vivo, activated T-cells migrate to the tumour site within the field of irradiation, however translational studies on the effects of radiotherapy on T-cell activation, function and activity are lacking. Methods: EAC patient (n = 6) PBMCs were isolated by density centrifugation in Ficoll Paque. T cells were activated and were irradiated at 1.8Gy, 3.6Gy bolus dosing and fractionation for 72 hrs. A panel of immune checkpoints, DAMPS, activation markers, and cytokines were assessed by flow cytometry. To determine the effect of the TME on T cells, PBMCs were cultured under conditions of nutrient deprivation (No Glucose & No Glutamine) under conditions of normoxia and hypoxia. We then ran the aforementioned panel by flow cytometry. We also activated PBMCs with immune checkpoint blockers to determine its effects on T cell expansion and survival. Results: 3.6Gy induced a significantly higher expression of DAPMS (Fig 1 p < 0.001); Calreticulin and HMGB1, most notably under conditions of nutrient deprivation (p < 0.001). Ionising radiation also resulted in an increase in the expression of cytokines and importantly in the context of targeted therapy, IR at both the conventional 1.8Gy and 3.6Gy induced a higher expression of checkpoints PD-1, PD-L1, TIGIT, and TIM-3 (p < 0.001). Interestingly, when T cells are activated in the presence of ICB (Atezolizumab, Pembrolizumab, Nivolumab), it increases the rate of T cell expansion, and enhances their survival compared to T cell activated only. (p < 0.001). Conclusion: This work demonstrates the impact of clinically utilised fractions of radiation, and conditions of the TME on T cell function and activity, with improved T cell expansion and survival in the presence of ICB's suggesting it may be a feasible combination therapy as an adjunct to radiotherapy.